Grassland biome: general description of the Pawnee site - Jameson, Donald A., author; Natural Resource Ecology Laboratory, Colorado State University, publisher (Colorado State University. Libraries, 1969)
The Pawnee Site, the Intensive Site location of the Grassland Biome, lies within the western division of the Pawnee National Grasslands which is administered by the U.S. Forest Service. At the western edge of the Pawnee National Grasslands lies the Central Plains Experimental Range operated by the Agricultural Research Service. Intensive studies requiring careful experimental control are conducted on the Central Plains Experimental Range; more extensive studies requiring a great deal of space but less control are conducted on the Pawnee National Grasslands.
Keywords: Central Plains Experimental Range; Pawnee National Grasslands; grassland experimental studies; Grasslands -- Colorado; Grassland ecology -- Colorado; Grassland conservation -- Colorado